2023
DOI: 10.1002/ohn.231
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐Guided Ethanol Ablation as a Primary Treatment for Thyroglossal Duct Cyst: Feasibility, Characteristics, and Outcomes

Abstract: Objectives. To evaluate the feasibility, characteristics, and outcomes of ultrasound-guided ethanol ablation (US-EA) as a primary treatment for thyroglossal duct cysts (TGDCs).Study Design. Prospective case series.Setting. Single center study.Methods. The inclusion criteria were as follows: (i) patients with TGDC aged ≥18 years, (ii) benign TGDC in imaging and cytological examinations, and (iii) patients' need for nonsurgical scarless treatment. US-EA was used as the primary treatment strategy. The primary out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(38 citation statements)
references
References 20 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…With respect to the specific EA technique, two major issues related to this study require clarification: (1) the volume of ethanol injection and (2) the retention or aspiration of the injected ethanol at the conclusion of EA. A literature review of seven studies on EA for TGDC published since 2010 revealed that five studies referenced 50% or more of the aspirate volume as the minimum limit for ethanol injection (up to 15 mL of ethanol) [7][8][9][10]16,19,22]. However, in the current study, a relatively small volume of ethanol was used (≤2.5 mL).…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…With respect to the specific EA technique, two major issues related to this study require clarification: (1) the volume of ethanol injection and (2) the retention or aspiration of the injected ethanol at the conclusion of EA. A literature review of seven studies on EA for TGDC published since 2010 revealed that five studies referenced 50% or more of the aspirate volume as the minimum limit for ethanol injection (up to 15 mL of ethanol) [7][8][9][10]16,19,22]. However, in the current study, a relatively small volume of ethanol was used (≤2.5 mL).…”
mentioning
confidence: 78%
“…For the first EA session, the median volumes of aspirate and injected ethanol were 3.0 mL (IQR, 2.0 to 8.0 mL) and 2.0 mL (IQR, 1.3 to 2.0 mL), respectively, Treatment efficacy was assessed using the VRR, calculated as ([initial volume-final volume]/initial volume×100%), and treatment success. A VRR of ≥70% was used as the cutoff value for defining success, rather than a VRR of ≥50%, to avoid overestimating the treatment efficacy of EA compared to SO [10,16]. For the SO group, the VRR was considered to be 100% if the TGDC was completely excised during surgery.…”
Section: Feasibility and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies comprising fewer than 200 patients in Korea, Hong Kong, and Turkey have demonstrated mean VRRs ranging from 73% to 96.2% at final follow-up examination [ 1-7 , 10 ]. The largest among them was performed by Park et al in Korea, with 77 patients undergoing EA for TGDC.…”
Section: Discussionmentioning
confidence: 99%
“…Another, less invasive treatment option for TGDCs is ultrasound-guided ethanol ablation (EA). EA is currently rarely used for TGDC in the United States; however, it has been used successfully in Europe and Asia for the last decade, with increasing frequency [ 1-7 , 10 ]. In this case report we describe the successful treatment of a TGDC with EA at our institution in the United States.…”
Section: Introductionmentioning
confidence: 99%